(untitled) (Journal of Forensic Medicine & Toxicology, 2025)
Background: Drowning is regarded as the primary cause of fatalities in aquatic environments and the third most prevalent form of accidental death globally, with the largest incidence rates occurring in underdeveloped nations. Accurate forensic diagnosis of drowning poses a problem because of the generic characteristics of post-mortem findings derived from traditional autopsy techniques. This study examines the importance of fluid in the paranasal sinuses in drowning incidents and aims to differentiate drowning from non-drowning instances. Methods: This was an observational descriptive comparative study done in fifty cases of drowning fatalities and fifty cases of other asphyxial fatalities who underwent medicolegal autopsy at the Department of Forensic Medicine, Government Medical College, Kannur. The paranasal sinuses were inspected for fluid during the medicolegal autopsy. Results: The study group consisted primarily of males (62.7%) with an average age of 46.90±16.34 years. Nearly half of them were in their fourth and fifth decades of life. In this study, 46 (92%) of the 50 drowning cases exhibited fluid in the paranasal sinuses (frontal, maxillary and sphenoid sinuses). None of the 50 instanc es of other asphyxial deaths showed fluid in the paranasal sinuses. The findings endorse the efficacy of para nasal sinus fluid analysis as a significant diagnostic tool in instances where drowning is suspected yet cannot be conclusively verified by conventional methods. Conclusion: This study demonstrated that the presence of fluid in the paranasal sinuses serves as a diagnostic indi cator of drowning-related death, corroborating other research. The physiological comprehension of fluid accumu lation in the paranasal sinuses of drowning victims and its forensic ramifications illustrate the importance of this diagnostic technique in medico-legal enquiries. The detection of fluid in these sinuses offers insights into the phys iopathology of drowning and serves as a crucial instrument for distinguishing between drowning and non-drown ing incidents, thus facilitating the precise identification of the cause of death and assisting in criminal enquiries.